The role of attention and emotions in fundraising processes - a qualitative analysis - Walter, Jonas Wolfgang (2022)
This paper studies the role of attention and emotions in fundraising processes. It presents and analyzes four core findings of a survey conducted among 15 high-level managers. Altogether, the four results imply that given stakeholder-type and diminishing marginal returns, managers should design the fundraising process in away that maximizes investors’ ex ante emotional receptiveness while optimizing for levels of involvement and attention. The subsequent discussion of these aspects crystallizes two managerial implications and suggests avenues for future research. I would like to thank all interviewees for contributing to my qualitative research study: Olaf Scheer, Michael Mandel, Peter Kreutter, Manuel Andrade, Stephan Schubert, Gerrit Seidel, Matthias Uebing, Jens Remmers, Olav Bouman, Bert Ohne mueller, Kerstin Schneider, Matthias Meyer-Schwarzenberger, Tania Rubenis, Mehmet Cabadak and Klaus Sailer